Analisis Realisasi Anggaran Untuk Menilai Efektivitas dan Efisiensi Kinerja Pada Badan Perencanaan Penelitian dan Pengembangan Kabupaten Kepulauan Aru - Piter Arson Welay; Agustina Saidekut (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to determine whether the realization of the budget to assess the effectiveness and efficiency of performance at the Research and Development Planning Agency of the Aru Islands Regency has been running effectively. The research location is the Research and Development Planning Agency of the Aru Islands Regency. The object of this research is the Budget Realization Report of the Research and Development Planning Agency of the Aru Islands Regency for the last 3 (three) years, namely the year 2017-2019 before Covid-19. The data analysis technique used is descriptive quantitative. Quantitative descriptive statistical analysis is a technique of analyzing data to summarize and describe numerical data for easy interpretation. The steps to analyze the data in this study are to calculate the Effectiveness Ratio Analysis and Efficiency Ratio based on the Budget Realization Report for the 2017 – 2019 Fiscal Year. The results of this study indicate that the budget realization analysis to assess the effectiveness and efficiency of performance can be said to have been effective and efficient. .